Sodium bicarbonate induces alkalosis, but improves high-intensity cycling performance only when participants expect a beneficial effect: a placebo and nocebo study - Zagatto, Alessandro Moura [UNESP]; Lopes, Vithor Hugo Fialho [UNESP]; Dutra, Yago Medeiros [UNESP]; de Poli, Rodrigo Araujo Bonetti [UNESP]; Dolan, Eimear; Rasica, Letizia; Murias, Juan M.; de Azevedo, Paulo Henrique Silva Marques (Springer Nature, 2024)
The study aimed to investigate the effects of sodium bicarbonate (NaHCO3) intake with divergent verbal and visual information on constant load cycling time-to-task failure, conducted within the severe intensity domain. Fifteen recreational cyclists participated in a randomized double-blind, crossover study, ingesting NaHCO3 or placebo (i.e., dextrose), but with divergent information about its likely influence (i.e., likely to induce ergogenic, inert, or harmful effects). Performance was evaluated using constant load cycling time to task failure trial at 115% of peak power output estimated during a ramp incremental exercise test. Data on blood lactate, blood acid–base balance, muscle electrical activity (EMG) through electromyography signal, and the twitch interpolation technique to assess neuromuscular indices were collected. Despite reduced peak force in the isometric maximal voluntary contraction and post-effort peripheral fatigue in all conditions (P < 0.001), neither time to task failure, EMG nor, blood acid–base balance differed between conditions (P > 0.05). Evaluation of effect sizes of all conditions suggested that informing participants that the supplement would be likely to have a positive effect (NaHCO3/Ergogenic: 0.46; 0.15–0.74; Dextrose/Ergogenic: 0.45; 0.04–0.88) resulted in improved performance compared to control. Thus, NaHCO3 ingestion consistently induced alkalosis, indicating that the physiological conditions to improve performance were present. Despite this, NaHCO3 ingestion did not influence performance or indicators of neuromuscular fatigue. In contrast, effect size estimates indicate that participants performed better when informed that they were ingesting an ergogenic supplement. These findings suggest that the apparently ergogenic effect of NaHCO3 may be due, at least in part, to a placebo effect.
Keywords: Blood acid–base balance; Cycling performance; Peripheral nerve stimulations; Placebo effect; Supplement expectation